2016
DOI: 10.1177/0954410015622964
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of a high pressure ratio centrifugal compressor by integrated cooling

Abstract: Centrifugal compressors with high pressure ratio have been widely used in small gas turbines, industrial compressors and turbochargers. High mechanical stress and high temperature of the impeller and large compression power required are the key factors that limit the pressure ratio achieved by centrifugal compressors. Cooling is an effective way to reduce the required compression power and the impeller temperature and it is widely used in gas turbines and industrial compressors. In this work, a cooling method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been set to be adiabatic in the numerical model, while in the experiment, it is very hard to control the heat transfer to surroundings, especially in a high pressure ratio. Moosania et al [14] reported that in a compressor, heat transfer to the surroundings considerably increases the compressor performances, especially in a high pressure ratio. Figure 6 illustrates the compressor total pressure ratio by cooling on different parts with varied cooling powers.…”
Section: Numerical Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been set to be adiabatic in the numerical model, while in the experiment, it is very hard to control the heat transfer to surroundings, especially in a high pressure ratio. Moosania et al [14] reported that in a compressor, heat transfer to the surroundings considerably increases the compressor performances, especially in a high pressure ratio. Figure 6 illustrates the compressor total pressure ratio by cooling on different parts with varied cooling powers.…”
Section: Numerical Model Validationmentioning
confidence: 99%
“…A secondary flow can flow inside some jackets attached to the walls to cool them down. Moosania et al [14] used shell cooling for all of the external walls in a centrifugal compressor. A huge improvement in the compressor performance, as well as a noticeable reduction in impeller temperature have been obtained by shell cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Heuer et al 3 successfully performed steady state CHT calculations combined with thermal stress analysis for a turbine housing and presented an optimization method in terms of stress reduction. Mostafa et al [4][5][6] analysed in detail the cooling of the external wall surfaces of different parts of a centrifugal compressor, including the casing, the vaneless diffuser and the backdisc, and found that integrated cooling could significantly improve the performance of the compressor in terms of pressure ratio, efficiency, compression power and maximum impeller temperature, and that the effect of the casing cooling was the most pronounced of the three. As turbine inlet temperature and compressor pressure ratio increase, there is a growing interest in cooling turbocharger more efficiently.…”
Section: Introductionmentioning
confidence: 99%